2020
DOI: 10.1016/j.celrep.2020.03.007
|View full text |Cite
|
Sign up to set email alerts
|

Lymph Node Stromal Cells Generate Antigen-Specific Regulatory T Cells and Control Autoreactive T and B Cell Responses

Abstract: Highlights d Lymph node stromal cells convert naive CD4 + T cells into T REG cells d Conversion of T REG cells by lymph node stromal cells is IL-2 dependent d Autoreactive T FH cells and B cells are controlled by lymph node stromal cells

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
63
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 51 publications
(66 citation statements)
references
References 71 publications
(98 reference statements)
3
63
0
Order By: Relevance
“…However, RA is an important risk factor [51] for this type of diabetes, possibly due to RA-driven inflammation [52]. Since it has been shown that murine LNSCs can control the formation of autoreactive T cells by presenting specific PTA in the context of MHC molecules [27,32,53], it is possible to speculate that LNSCs obtained from RA patients are not capable of suppressing RRAD-specific T cells due to lower expression of this PTA. Although the limitation of our study is the low number of PTAs we analyzed.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, RA is an important risk factor [51] for this type of diabetes, possibly due to RA-driven inflammation [52]. Since it has been shown that murine LNSCs can control the formation of autoreactive T cells by presenting specific PTA in the context of MHC molecules [27,32,53], it is possible to speculate that LNSCs obtained from RA patients are not capable of suppressing RRAD-specific T cells due to lower expression of this PTA. Although the limitation of our study is the low number of PTAs we analyzed.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, expression and subsequent presentation of PTAs by LNSC in the context of MHC class II to CD4+ T cells can also lead to maintenance of T regs [31]. Moreover, recently we demonstrated that LNSCs convert naïve autoreactive CD4+ T cells into antigen-specific T regs cells and suppress autoreactive T follicular helper (T fh ) and B cells responses [32].…”
Section: Introductionmentioning
confidence: 99%
“…Recently, a novel organoid composed of cells derived from lymph node and tumor tissue from the same patient was developed to evaluate the efficacy of immunotherapy and to assess the relationship between the clinical response of the patient to therapy ( 163 ). Lymph node stromal cells (LNSCs) have been reported to be involved in the inhibition of early activation of autoreactive immune cells and peripheral tolerance ( 164 ). Mechanisms can be clarified using this advanced organoid model.…”
Section: Challenges and Future Developmentsmentioning
confidence: 99%
“…Murine LNSCs can additionally acquire from DCs peptide–MHCII complexes that they present to CD4 + T cell in order to promote their dysfunction ( Figure 2 A) [ 51 ]. MHCII expression by LECs and FRCs has been shown to play important roles in Treg homeostasis in mice ( Figure 2 A) [ 52 , 53 ]. Our laboratory recently demonstrated that abolition of genetic MHCII expression in murine LNSCs, especially in LECs, impacts Treg proliferation in LNs and leads to the development of spontaneous features of autoimmunity in elderly mice [ 54 ].…”
Section: Lnscs Function As a Brake For The Development Of T Cell-mmentioning
confidence: 99%